2000
DOI: 10.15760/etd.416
|View full text |Cite
|
Sign up to set email alerts
|

Chronology and Ecology of Late Pleistocene Megafauna in the Northern Willamette Valley, Oregon

Abstract: This study is an investigation of the timing of extinction of late Pleistocene, large bodied mammalian herbivores (megafauna) and of the environment in which they lived.The demise of the megafauna near the end of the Pleistocene remains unexplained.Owing to potential human involvement in the extinctions, archaeologists have been particularly concerned to understand the causes for faunal losses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Overall, the specimens were in good condition based on visual criteria, and high collagen content (see isotopic analysis below) supports the conclusion that the specimens did not suffer from much post-depositional exposure and reworking. In short, the Willamette Valley megafaunal remains we studied do not reflect "kill sites" or other types of archaeological sites, but are in-situ remains of natural death and deposition of animals that once lived in the valley (Gilmour, 2011).…”
Section: Fossil Megafaunal Sites and Materialsmentioning
confidence: 99%
“…Overall, the specimens were in good condition based on visual criteria, and high collagen content (see isotopic analysis below) supports the conclusion that the specimens did not suffer from much post-depositional exposure and reworking. In short, the Willamette Valley megafaunal remains we studied do not reflect "kill sites" or other types of archaeological sites, but are in-situ remains of natural death and deposition of animals that once lived in the valley (Gilmour, 2011).…”
Section: Fossil Megafaunal Sites and Materialsmentioning
confidence: 99%
“…The δ 15 N values ranged from 6.44 to 10.12, average 7.93. Two individuals from the Willamette Valley, Oregon had δ 13 C values of-20.8 and-21 and δ 15 N values of 7.4 and 6.6 indicating they were feeding primarily on C3 vegetation in a palaeoenvironment of open grassland and sparse canopy (Gilmour et al, 2015). The inferred diet of P. harlani from Valsequillo, Mexico based on δ 13 C indicated that this individual was primarily a grazer (Pérez-Crespo et al, 2014), while two samples from Térapa, Sonora produced quite different δ 13 C values of −6.3 and −0.5 similar to other taxa from the site and supported the interpretation of a mosaic of habitats that supported a variety of herbivores with different dietary preferences.…”
Section: Paramylodon Harlanimentioning
confidence: 99%
“…The Columbia River would have provided an unimpeded passageway east through the Cascade Range onto the Columbia Plateau. There is little evidence of Clovis along the Columbia River itself, although the Willamette River drainage, the first major inland tributary of the Columbia River, has extensive evidence of megafauna remains (Gilmour et al 2015) and isolated Clovis points (Connolly 1994).…”
Section: North Pacific Coast Origin Of Clovis Technologymentioning
confidence: 99%